What constitutes professional communication in aviation: Is language proficiency enough for testing purposes?. (July 2018) - Kim, Hyejeong
This paper aims to identify what aviation experts consider to be the key features of effective communication by examining in detail their commentary on a 17-minute segment of recorded radiotelephony discourse between a Russian pilot and a Korean air traffic controller. The segment was played to three practising pilots and three air traffic controllers. Their commentary on the qualities of communication displayed in the interaction was recorded and coded thematically, using a grounded ethnography approach. The analysis revealed that although the Russian pilot was viewed as having limited English proficiency, the strategies he used to make himself understood were evaluated positively as fulfilling the requirements of the professional role. By contrast, the Korean air traffic controller, although not evaluated as having limited proficiency, was criticized for his lack of professional knowledge. The discourse analysis and the feedback given by these expert informants highlight not only the nature of the miscommunication arising in unexpected situations, but also the multiple factors that may contribute to it. While language proficiency is clearly an issue, there are many other sources of miscommunication that emerge during the exchange. These findings are used to critique the narrow, language-focused oral proficiency construct as articulated in the holistic descriptors and the rating scale stipulated by the International Civil Aviation Organization (ICAO, 2010) as the basis for tests of aviation English worldwide. Instead the paper proposes an expanded construct of oral communication incorporating elements of professional knowledge and behaviour with a focus on interactional competence specific to this context.